2007
DOI: 10.1109/iembs.2007.4353419
|View full text |Cite
|
Sign up to set email alerts
|

Time dependency assessment of muscular fatigue index and hand tremor under operating conditions

Abstract: The aim of this paper is to determine if operating has an effect on a surgeon's muscular fatigue and hand tremor. Electromyography and tremor measurements were taken throughout a day of operating from the brachioradialis (BR) and mid deltoid (MD) muscles of six head and neck surgery consultants and two Ear, Nose, and Throat (ENT) registrars. The percent change in Mean Frequency (MF) of their EMG signal and tremor amplitudes was compared to twenty normal controls performing desk work. It was found that operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It has been argued that during prolonged operating, muscular fatigue can develop and result in a decrement in a surgeon's fine motor control (Masters, Poolton, Abernethy, & Patil, 2008;Slack, Coulson, Ma, Webster, & Proops, 2008;Slack & Ma, 2007). Future studies are needed to determine whether muscular fatigue may affect finger pinch movement discrimination ability and how instrument elastic resistance may affect the rate of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that during prolonged operating, muscular fatigue can develop and result in a decrement in a surgeon's fine motor control (Masters, Poolton, Abernethy, & Patil, 2008;Slack, Coulson, Ma, Webster, & Proops, 2008;Slack & Ma, 2007). Future studies are needed to determine whether muscular fatigue may affect finger pinch movement discrimination ability and how instrument elastic resistance may affect the rate of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Though the results based on Levinson-Durbin algorithm (LD algorithm) show faster convergence than LMS (Least Mean Square) and RLS (Recursive Least Squares) algorithms, however, it does not detect amplitude and frequency range of a tremor at a given specific time. In addition, no effort to date specifically addresses tremors in different frequency bands, though it has been shown that different kinds of tremor have different characteristics [4], [5].…”
Section: Introductionmentioning
confidence: 98%
“…It requires a higher level of precision and accuracy of the surgeons' hand movements, where FIT is the primary hindrance. Hand tremor studies have been reported earlier by several groups on manipulation of hand‐held microsurgical devices . However, a thorough analysis of fatigue induced hand tremor in laparoscopic tool manipulation has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, a thorough analysis of fatigue induced hand tremor in laparoscopic tool manipulation has not been reported so far. Even though several studies have shown that long‐term training increases the accuracy of the LTM, effect of FIT in such cases were not addressed . Since laparoscopic surgeries are comparatively longer in time with respect to open surgeries, generation of muscle fatigue is also very common in these cases which affect the accuracy of the surgical procedure causing tremor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation